PENGUATAN KARAKTER PADA ANAK YANG BERKONFLIK DENGAN HUKUM MELALUI PROGAM REHABILITASI UNTUK MEMBENTUK WARGA NEGARA YANG BAIK (STUDI PADA YAYASAN SAHABAT KAPAS) - Sri Rahayu; Dewi Gunawati; Triana Rejekiningsih (Jurnal PPKn, 2019)
This study aims to determine: 1) The importance of strengthening character in children in conflict with the law through rehabilitation programs by Sahabat Kapas; 2) Efforts to strengthen character in children who are in conflict with the law by Sahabat Kapas; 3) The impact of strengthening the character of children in conflict with the law by Sahabat Kapas; 4) Constraints faced in strengthening character in children who are in conflict with the law by Sahabat Kapas. This study uses a qualitative approach with descriptive qualitative. Data collection uses observation, interviews, and document analysis. Testing the validity of the data using an interactive analysis model.  Conclusion of the research results: 1) Strengthening the character of the AKH (Children in Conflict with the Law) is important because children in detention centers (detention centers) still cannot show good behavior, such as: hitting each other, asking for and forcing, due to several factors including boredom when in detention, therefore it is important to provide assistance in order to restore the psychological condition of the child 2) Efforts to strengthen character through rehabilitation programs are carried out with three types of assistance which include; psychological assistance (children are given the opportunity to convey their complaints), psychosocial assistance (planting values so that children can integrate with the community when they leave later), and economic value skills (making handicrafts and other works) using individual methods and group. 3) The impact of character strengthening on AKH including: a) more open children; b) children are more confident; c) creative; d) attitudes toward others are more positive. But the legal awareness shown by the AKH when it came out of the detention center still tended to be low, this was indicated by their behavior which tends to deviate again, such as revenge, committing a crime, to recidivism. 4) Constraints faced in character strengthening are grouped into two, namely: a) Internal constraints, including lack of human resources and SOP for mentoring that is not optimal; b) External Constraints, which include; community stigma against AKH which tends to be negative and restoration of AKH behavior which still requires long-term and  continuous time.   Full Paper